The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11064-012-0729-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Iron, Vitamin B12 and Folic Acid Levels in Parkinson’s Disease

Abstract: We aimed to investigate possible associations between systemic iron metabolism deficiency and Parkinson's disease, and also to research any possible correlations between stage of the disease and vitamin B12 and folic acid levels. 33 male and 27 female patients diagnosed with idiopathic Parkinson's disease and 22 male and 20 female age- and sex-matched controls were enrolled in the study. Having the diagnosis of secondary Parkinsonism or Parkinson plus syndromes, and for the females, not being in the menopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
5
30
1
2
Order By: Relevance
“…The same consideration can be made about the biological effect of sex on metals. In fact, when we adjusted our biochemical findings for sex effect, no difference in ferritin levels was detected between patients and controls, in agreement with recent studies [23,24]. The sex effect resulted evident when we carried out a multivariate stepwise logistic regression considering all the biological and demographic variables.…”
Section: Discussionsupporting
confidence: 90%
“…The same consideration can be made about the biological effect of sex on metals. In fact, when we adjusted our biochemical findings for sex effect, no difference in ferritin levels was detected between patients and controls, in agreement with recent studies [23,24]. The sex effect resulted evident when we carried out a multivariate stepwise logistic regression considering all the biological and demographic variables.…”
Section: Discussionsupporting
confidence: 90%
“…A number of micronutrients have been identified as being important in PWP, including calcium, vitamin D and vitamin B12 . However, these were not consistently assessed by the surveyed dietitians.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, folate intake eight years prior to diagnosis of Parkinson's disease was associated with olfactory dysfunction and disease risk in Swedish patients (52,84). In contrast, the Honolulu-Asia Aging Study cohort and case-control studies from three regions in China (N > 6,000) found no relationship between folate or vitamin B 12 intake or status and risk for Parkinson's disease (53,113,114). However, a recent meta-analysis of 14 studies found that elevated plasma Hcy was an independent risk factor for Parkinson's disease (96,115,116).…”
Section: Folatementioning
confidence: 98%
“…Further, as Parkinson's disease progressed levels of vitamin B 12 decreased, and low B 12 was associated with greater disease severity (113,116). However, no clear relationship between vitamin B 12 intake and the risk of Parkinson's disease has been demonstrated (53,113,114,116).…”
Section: Vitamin B 12mentioning
confidence: 99%